A Randomized Controlled Study of Caudal Dexmedetomidine for the Prevention of Postoperative Agitation in Children Undergoing Urethroplasty - Weichao Zhu; Jie Sun; Jianhua He; Jianhua He; Wangping Zhang; Meng Shi (Frontiers Media S.A., 2021)
Background: Postoperative agitation is a common complication in children undergoing general anesthesia. This study aimed to investigate the effect of caudal dexmedetomidine for the prevention of postoperative agitation in children undergoing urethroplasty.Materials and Methods: Eighty children were prospectively recruited to this study and randomized to two groups (40 cases in each group), specifically, a dexmedetomidine group (group D) who received 0.2% ropivacaine + 0.5 μg/kg dexmedetomidine for caudal block, and a control group who received 0.2% ropivacaine alone. The time to wake up, the time to discharge from the postanesthesia care unit (PACU), the duration of the caudal block, and the Ramsay sedation scale (RSS) were evaluated in the patients. Adverse events such as postoperative agitation, respiratory depression, bradycardia, hypotension, excessive sedation, nausea, and vomiting were also recorded during the first postoperative 24 h.Results: The incidence of postoperative agitation was lower in group D compared with patients in the control group (2.5 vs. 22.5%, p = 0.007). The time to wake up and the time to discharge from PACU were longer in group D than in the control group (15.2 ± 2.6 vs. 13.4 ± 1.3 min, 48.2 ± 7.7 vs. 41.5 ± 8.0 min, respectively, p < 0.001). However, the extubation times were similar between the two groups. The duration of the caudal block was longer in group D compared with the control group (8.8 ± 1.6 vs. 4.6 ± 0.7 h, p < 0.001).Conclusions: Caudal dexmedetomidine prolongs the duration of caudal block and decreases the incidence of postoperative agitation in children undergoing urethroplasty.Clinical Trial Registration: ChiCTR1800016828.